Manual therapy in diaphragm muscle: effect on respiratory muscle strength and chest mobility - Braga, Darling Kescia Araújo Peixoto; Marizeiro, Débora Fortes; Florêncio, Ana Carolina Lins; Teles, Mariana Dias; Silva, Ítalo Caldas; Santos-Júnior, Francisco Fleury Uchôa; Campos, Nataly Gurgel (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Manual therapy uses the hands as a form of healing, being a manipulation for therapeutic purposes. However, there is little evidence of its effects on the respiratory system. Objective: To describe the effect of manual therapy on the diaphragm, on respiratory muscle strength and on the mobility of the thoracic cavity. Method: Descriptive, longitudinal, interventional and quantitative research, performed at the Cardiopneumofunctional Physical Therapy Laboratory of the Federal University of Ceará (UFC). The sample consisted of 40 sedentary female students, aged between 18 and 35 years of the Physiotherapy course of the UFC. The following techniques were performed: “diaphragm lift” and double diaphragm. Data collection was performed in three steps, on the same day and by the same researcher, under a homogeneous verbal command. It was considered statistically significant value of p≤0,05. Results: After applying the techniques, a comparative analysis was performed, which demonstrated a statistically significant difference in the maximum expiratory pressure, with p< 0,0001, and all the coefficients of the cirtometry, being p<0,0025 (axillary), p<0,0085 (xiphoid) and p<0,0005 (basal). Conclusion: Manual therapy techniques performed on the diaphragm exert an influence on muscle strength due to the increase in maximum expiratory pressure and in the mobility of the thoracic cavity, reflected in the increase of the coefficients of the cirtometry.